ASSESING THE RELATIONSHIP BETWEEN DYNAMIC CAPABILITIES AND SUPPLY CHAIN RESILIENCE FOR BUMIPUTERA SME CONTRACTORS: KEY CONTRIBUTORS, RESEARCH HOTSPOTS - Jamaludin, Shariffah Zatil Hidayah Syed; Mustapa, Muzani; Ramly, Zuhaili Mohamad (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The occurrence of supply chain disruptions, intensified by the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) in modern business scenarios, highlights the urgent need for robust strategies to mitigate their influence on business performance. Small and Medium Enterprise (SME) contractors face numerous challenges and vulnerabilities in supply chain management SCM activities, necessitating the establishment of a Supply Chain Resilience (SCRE) framework, primarily aimed at enhancing business continuity. Unlike larger firms, Bumiputera SMEs often lack essential resources and capabilities to manage these disruptions, rendering them particularly vulnerable. Therefore, this study identifies the key themes that integrate SCRE, considering its associations with Dynamic Capabilities (DC). A bibliometric analysis was performed employing performance assessment and scientific visualisation techniques. Data were extracted from the Scopus database and analysed by VOSviewer. The methodology encompasses a systematic framework, including defining search criteria, data analysis, network visualisation, and thematic clustering to identify structural and evolutionary patterns in SCRE. The findings emphasised that ‘supply chain resilience’ is a central theme, strongly linked to DCs, supply chain management, and organisational resilience. Furthermore, deficiencies in this study have been identified, especially in emerging markets and the role of DCs in SCRE. The results of this investigation will provide a comprehensive overview of the DCs and SCRE, thereby providing theoretical and practical implications for academicians, policymakers, and industry stakeholders. The study lays the groundwork for future research directions that aim to advance DCs and SCRE in the construction sector.